Exposure to adverse childhood experiences and early initiation of electronic vapor product use among middle school students in Nevada. (June 2020) - Williams, Lauren; Clements-Nolle, Kristen; Lensch, Taylor; Yang, Wei
Highlights: 1 in 5 middle school students had used EVPs and 5.1% initiated before age 11. A strong graded relationship between cumulative ACEs and early initiation of EVPs was observed. Hispanic, rural, and military family students were also at risk for early initiation of EVPs. Abstract: Introduction: The use of electronic vapor products (EVPs) among youth has increased significantly in recent years, yet little is known about factors associated with initiation of EVPs during early adolescence. The purpose of this study was to explore the relationship between chronic exposure to adverse childhood experiences (ACEs) and early initiation of EVPs in a representative sample of middle school students. Methods: 5, 464 students from 113 middle schools (grades 6–8) completed the Nevada Youth Risk Behavior Survey (YRBS) in the spring of 2017. Six abuse and household dysfunction measures were used to calculate a cumulative ACE score (range 0–6). Initiation of EVPs (e-cigarettes, e-cigars, e-pipes, vape pipes, vaping pens, e-hookahs, and hookah pens) before age 11 was considered early initiation. Weighted logistic regression was used to assess the relationship between cumulative ACE exposure and early initiation of EVPs after controlling for sex, age, race/ethnicity, rurality, free or reduced lunch status, and military family involvement. Results: Nearly 1 in 5 middle school students (18.6%) reported using EVPs, 6.7% had used EVPs during the past 30 days, and 5.1% started using EVPs before age 11. After controlling for sociodemographics, a strong graded relationship between cumulative ACE exposure and early initiation of EVPs was observed: 1 ACE (AOR = 1.60; 95% CI = 0.99–2.59), 2 ACEs (AOR = 2.29; 95% CI = 1.33–3.93), and 3–6 ACEs (AOR = 3.43, 95% CI = 2.20–5.36) compared to no ACEs. Conclusions: Screening for ACEs in school-based settings may be a feasible approach for identifying students who may be at-risk for early initiation of EVPs.